Conservative and Radical Surgery vs. BRAF-Target Therapy for Recurrent Ameloblastoma - Dimas Bramanto Satrya Utama; Nadia Maulida Andini; Afif Surya Adena (Majalah Biomorfologi, 2025)
Highlights Ameloblastoma is a widely discussed odontogenic tumor, yet research on less invasive treatment options for recurrent cases remains limited. BRAF-targeted therapy offers a less invasive approach that may reduce the extent of surgical intervention required.   ABSTRACT Background: Ameloblastoma is a benign odontogenic tumor that can affect surrounding tissues and is prone to recurrence if not completely excised. Surgical therapy is currently the primary treatment modality. However, recurrences are common following prior surgical interventions. Recently, a novel approach involving BRAF (B-Rapidly Accelerated Fibrosarcoma)-targeted therapy has been introduced, aiming to prevent molecular mutations. This therapy is non-invasive, but its efficacy in treating recurrent ameloblastoma remains uncertain. Objective: This article aimed to compare the outcomes of conservative and radical surgery with BRAF-targeted therapy in the management of recurrent ameloblastoma. Material and Method: An electronic search was conducted using the PubMed and Scopus databases. Relevant studies were selected based on predefined inclusion criteria. Results: A total of nine studies were included in the analytical synthesis. Recurrence in ameloblastoma is often due to residual tumor tissue located in anatomically challenging areas following surgery. BRAF-targeted therapy has emerged as a promising option for patients with recurrent disease, offering precise tumor targeting and potentially reducing the need for further surgical intervention. Conclusion: Surgical and BRAF-targeted therapies each offer benefits in managing recurrent ameloblastoma. While recurrence is often linked to residual tumors in complex anatomical areas, BRAF-targeted therapy provides a non-invasive, precise alternative—especially for patients with multiple recurrences. It can reduce tumor size, improve lesion localization, and potentially limit the need for extensive surgery.